Plagiarism Norms and Practices in Coursework Assignments - Ting, Su Hie; Muriatul Khusmah, Musa; Mah, Florence Sau-Fong (Macrothink Institute, 2014)
The study compared the plagiarism norms and practices among pre-university, diploma and degree students. The specific aspects examined were perceived necessity to include citations in assignments, preferred penalties for plagiarism, and academic writing practices. The questionnaire responses of 263 students from three levels of university education were analysed. The results showed that the perceived necessity for attribution in assignments is the highest for the degree students but the norm to require citations and to penalise omission of citations is not extensive at all three levels. A majority of the students felt that plagiarism should be penalised but preferred warning from their lecturer, assignment resubmission and counselling. Mosaic plagiarism is the most common whereby students combine texts from the same source or different sources without proper citation and referencing. The most common unethical help-seeking behaviour is copying another student’s work. The findings suggest that while lack of knowledge on citation and referencing may lead to improper or non-attribution of sources, plagiarism cannot be dealt with by instruction on citation and referencing alone as respect for intellectual property can only be inculcated by treating plagiarism as a serious academic misdemeanour.